2022
DOI: 10.3324/haematol.2022.280815
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality of sickle cell disease patients is unaffected by splenectomy: evidence from three decades of follow-up in a high-income setting

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Few reports have compared the SS and Sβ 0 phenotypes, but Sβ 0 patients might be more prone to persistent splenomegaly 6,7 and ASS 8 ; characteristics that may result in a higher rate of splenectomy, as observed as early as 1979 9 and in a recent Italian cohort (n = 534, 187 SS and 176 Sβ 0 ) showing that 53% of Sβ 0 patients had a history of splenectomy versus 9.6% of SS patients. 2 Coexistent α-thalassaemia may also cause persistent splenomegaly. 10…”
Section: Increased Risk Of Venous Thromboembolism In Splenectomized P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports have compared the SS and Sβ 0 phenotypes, but Sβ 0 patients might be more prone to persistent splenomegaly 6,7 and ASS 8 ; characteristics that may result in a higher rate of splenectomy, as observed as early as 1979 9 and in a recent Italian cohort (n = 534, 187 SS and 176 Sβ 0 ) showing that 53% of Sβ 0 patients had a history of splenectomy versus 9.6% of SS patients. 2 Coexistent α-thalassaemia may also cause persistent splenomegaly. 10…”
Section: Increased Risk Of Venous Thromboembolism In Splenectomized P...mentioning
confidence: 99%
“…1 In addition, unpredictable complications, such as acute splenic sequestration (ASS) and hypersplenism, may require surgical splenectomy in up to 30% of patients. 2 Some authors have reported an increase in acute chest syndrome (ACS) and vaso-occlusive crisis (VOC) in the few years following the procedure in children, 3 but data on the long-term consequences of splenectomy in SCD adults are scarce. In conditions other than SCD, increases in venous thromboembolic events (VTEs) and pulmonary hypertension (PHT) have been reported following splenectomy.…”
Section: Increased Risk Of Venous Thromboembolism In Splenectomized P...mentioning
confidence: 99%
“…In a letter to the editor published in this issue of Haematologica, Pinto et al (10) compared survival and long-term complications in splenectomised and non-splenectomised individuals with SCD in Italy.…”
mentioning
confidence: 99%
“…There is a general paucity of research on the spleen in SCD. Although the study by Pinto et al (10) provides much needed novel evidence on the absence of long-term mortality related to surgical splenectomy, data on potential benefits of splenectomy are still sparse. Overall, international guidelines on the management of ASS and hypersplenism are lacking and recommendations for surgical splenectomy are based on weak evidence and pertain to all types of SCD despite genotypic variations in age and clinical presentation (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation